2015
DOI: 10.1177/1753465815599345
|View full text |Cite
|
Sign up to set email alerts
|

The role of inhaled prostacyclin in treating acute respiratory distress syndrome

Abstract: Acute respiratory distress syndrome (ARDS) is a syndrome of acute lung injury that is characterized by noncardiogenic pulmonary edema and severe hypoxemia second to a pathogenic impairment of gas exchange. Despite significant advances in the area, mortality remains high among ARDS patients. High mortality and a limited spectrum of therapeutic options have left clinicians searching for alternatives, spiking interest in selective pulmonary vasodilators (SPVs). Despite the lack of robust evidence, SPVs are common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 41 publications
1
55
0
1
Order By: Relevance
“…Furthermore, in vitro evidence of direct antiviral activity against SARS-CoV was studied and the genetic similarity between SARS-CoV and SARS-CoV-2 suggests their potential effectiveness against SARS-CoV-2 [96]. For iEPO, dosages up to 50 ng/kg per minute have been used [93,94,97,98]. Previous studies reported that to provide a clinically important increase in PaO2 and reduction in pulmonary artery pressure, the most effective and safe dosage appears to be 20-30 ng/kg per minute in adults and 30 ng/kg per minute in pediatric patients [98].…”
Section: Nitric Oxide and Epoprostenolmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in vitro evidence of direct antiviral activity against SARS-CoV was studied and the genetic similarity between SARS-CoV and SARS-CoV-2 suggests their potential effectiveness against SARS-CoV-2 [96]. For iEPO, dosages up to 50 ng/kg per minute have been used [93,94,97,98]. Previous studies reported that to provide a clinically important increase in PaO2 and reduction in pulmonary artery pressure, the most effective and safe dosage appears to be 20-30 ng/kg per minute in adults and 30 ng/kg per minute in pediatric patients [98].…”
Section: Nitric Oxide and Epoprostenolmentioning
confidence: 99%
“…For iEPO, dosages up to 50 ng/kg per minute have been used [93,94,97,98]. Previous studies reported that to provide a clinically important increase in PaO2 and reduction in pulmonary artery pressure, the most effective and safe dosage appears to be 20-30 ng/kg per minute in adults and 30 ng/kg per minute in pediatric patients [98]. For iNO, therapy was given for ≥ 3 days (30 ppm on day 1, followed by 20 and 10 ppm on days 2 and 3, respectively, then weaned on day 4) in a pilot study on SARS-CoV [99].…”
Section: Nitric Oxide and Epoprostenolmentioning
confidence: 99%
“…9,13,14 Iloprost, the stable carbacyclin derivative of prostacyclin (PGI 2 ), is a potent pulmonary vasodilator that lowers RV afterload at least as effectively as inhaled NO. 15 Moreover, iloprost and PGI 2 improved biventricular performance, [16][17][18] exerted anti-inflammatory effects, 19 ameliorated myocardial ischemia-reperfusion injury, 20 improved oxygenation in adult respiratory distress syndrome, 21 attenuated pulmonary ischemiareperfusion injury, 22 improved the pulmonary clearance of endothelin, 23 and reduced oxidative stress and counteracted platelet activation with consecutive microthrombosis. 24 On the background of these beneficial effects, we hypothesized that the prophylactic inhalation of iloprost would improve perioperative morbidity and outcome in patients undergoing elective heart surgery with ECC and at an increased risk for perioperative RV failure.…”
Section: Résumémentioning
confidence: 99%
“…Iloprost 110 29 [24][25][26][27][28][29][30][31][32][33][34][35][36][37] 119 26 [20][21][22][23][24][25][26][27][28][29][30][31][32] 121 27 [22][23][24][25][26][27][28][29][30][31][32] 121 30 [25][26][27][28][29][30][31][32][33][34] 114 30 [25][26][27][28]…”
Section: 11unclassified
“…, Searcy et al . ). Therefore, there is a clear need for novel therapeutic strategies for these conditions as well as a more profound understanding of the underlying pathophysiological mechanisms.…”
mentioning
confidence: 97%